The importance of mass balance in life cycle assessment of nature-based solutions for wastewater treatment: key learning points from a case study - Dufosse, K.; Forquet, N.; Molle, P.; Pradel, M.; Loiseau, E. (IWA Publishing, 2025)
This study aims to perform a comprehensive life cycle assessment (LCA) of nature-based solutions (NBS) for wastewater treatment (WWT), specifically focusing on a French vertical flow (VF) wetland. The LCA encompasses the construction phase, operational phase, and end-of-life management, with a particular emphasis on achieving a balanced mass flow for carbon, nitrogen, and phosphorus across air, water, and soil compartments. The VF wetland is evaluated for its environmental impacts and compared to a conventional activated sludge system. The key findings reveal that the VF wetland achieves substantial reductions in resource use, yet requires significantly more land and exhibits higher impacts on greenhouse gas emissions and in categories sensitive to water emissions. The results underline the importance of complete mass balances in LCA of NBS to accurately identify environmental hotspots. Recommendations for methodological improvements and system boundary definitions are provided to enhance the definition of mass balance within NBS.